2023
DOI: 10.3390/su15097206
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital, Firm Performance, and Sustainable Growth: A Study on DSE-Listed Nonfinancial Companies in Bangladesh

Abstract: Intellectual Capital (IC) stimulates corporate competitive advantages that can enhance firm performance and sustainable growth (SG). This study investigates IC’s affinity with and impact on accounting and market performance and SG of listed nonfinancial companies in Bangladesh. Data were collected from 69 nonfinancial companies for five years during 2017–2021, forming 345 observations. Modified Value Added Intellectual Coefficient (MVAIC) and steady-state models consecutively measured IC efficiency and Sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Some earlier studies, like Kongkuah et al (2021), Wasara and Ganda (2019), Iheduru and Chukwuma (2019), Chinedu et al (2019), Sohel Rana and Hossain (2023), and Sukmadilaga et al (2023 found a negative and significant link between the variables. Further investigation by Onuora and Christian (2019) revealed that environmental expenses had a negative and minor influence on the ROCE of 11 listed Nigerian oil and gas companies over the years 2017 and 2018.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 78%
“…Some earlier studies, like Kongkuah et al (2021), Wasara and Ganda (2019), Iheduru and Chukwuma (2019), Chinedu et al (2019), Sohel Rana and Hossain (2023), and Sukmadilaga et al (2023 found a negative and significant link between the variables. Further investigation by Onuora and Christian (2019) revealed that environmental expenses had a negative and minor influence on the ROCE of 11 listed Nigerian oil and gas companies over the years 2017 and 2018.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 78%
“…The following formula is utilized as the accounting-based performance measures of a firm: Hayes, 2021, Ali, Mahmud, and Lima, 2016, Rana & Hossain, 2023.…”
Section: Firm Performance Variablesmentioning
confidence: 99%
“…The natural logarithm of the total assets is applied for determining the firm size (Abad et al, 2017;Ducassy & Guyot, 2017;Islam, 2023). The firm age is calculated as the natural logarithm of the number of years after a company first registered on a stock market (Nguyen et al, 2015;Ammari et al, 2016, Rana & Hossain, 2023Agyemang et al, 2023). The last measure of corporate financial leverage is the proportion of total debt to total assets (Dey et al, 2018;Deswanto & Siregar, 2018).…”
Section: Control Variablesmentioning
confidence: 99%